Organomineral fertilizer application enhances Perilla frutescens nutritional quality and rhizosphere microbial community stability in karst mountain soils - Li, Ying; Shen, Qi; An, Xiaochi; Xie, Yuanhuan; Liu, Xiuming; Lian, Bin (Frontiers in Microbiology, 2022)
Introduction Applications of organomineral fertilizer (OMF) are important measures for developing organic agriculture in karst mountain areas. However, the influence of OMF on the structure and function of soil microbial diversity and their relationship with crop yield and quality are still unclear. Methods Based on soil science, crop science, and high-throughput sequencing methods, we investigated the changes of rhizosphere soil microbial communities of Perilla frutescens under different fertilization measures. Then, the relationship between P. frutescens yield and quality with soil quality was analyzed. Results The results showed that the addition of OMF increased the amount of total carbon and total potassium in soil. OF, especially OMF, improved P. frutescens yield and quality (e.g., panicle number per plant, main panicle length, and unsaturated fatty acid contents). Both OF and OMF treatments significantly increased the enrichment of beneficial microorganism (e.g., Bacillus, Actinomadura, Candidatus_Solibacter, Iamia, Pseudallescheria, and Cladorrhinum). The symbiotic network analysis demonstrated that OMF strengthened the connection among the soil microbial communities, and the community composition became more stable. Redundancy analysis and structural equation modeling showed that the soil pH, available phosphorus, and available potassium were significantly correlated with soil microbial community diversity and P. frutescens yield and quality. Discussion Our study confirmed that OMF could replace CF or common OF to improve soil fertility, crop yield and quality in karst mountain soils.